Post Hatch Developmental Changes in the Harderian Gland of Chicken - Rana, Jigyasa; Banubakode, S.B.; Nandeshwar, N.C.; Charjan, Rupali; Mainde , U.P. (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
The present study was aimed to study histomorphological changes in the Harderian gland of chicken from 3 day of hatch to 24 day old. The gland was compound tubule-acinar type, consisted of capsule, parenchyma and stroma. In post hatch group of chicks, the gland was surrounded by thin connective tissue capsule from which septae extend which subdivide the gland into lobules of varying size. In the parenchyma of the gland, acini situated at the periphery and tubules at the centre of lobule. The acini were lined by columnar epithelial cells of varying height with basally located nucleus and the tubular systems were lined by a single layer of epithelium varying from columnar to cuboidal. Stroma or interstitial tissue consisted of collagen, fibroblasts, blood vessels, nerves and immune cells, plasma cells and lymphocytes. The plasma cells increased with advancement of age. Secretory units of the gland secreted its material by blebs formation on the luminal surface epithelium at early post hatch groups, which subsequently released by disintegration of the cells in the advanced age.